The optical and electrochemical properties of ZnS/CdSe CO-Sensitized TIO2 solar cells - Nguyen, Thành Phương; Lam, Quang Vinh; Le, Minh Tuấn (Journal of Technical Education Science, 2014)
Quantum dots sensitized nanocrystalline TiO2 solarcells (QDSSCs) are promising thirdgeneration photovoltaic devices. In this study, CdSe quantum dots (Qds) have been prepared via a colloidal route using Mercaptoethanol (Thioglycol) (HOCH2CH2SH) as a capping agent, ZnS/CdSe co-sensitized TiO2 photoanodes for QDSSCs were prepared by ionic layer adsorption and reaction (SILAR) for improving overall photoconversion efficiency. The structural of materials the TiO2/CdSe/ZnS, optical, morphological and photoelectrochemical properties of anode TiO2/CdSe/ZnS thin films were investigated by optical spectrum, TEM, FE- SEM, X-Ray.